Synthesis of benzamides, and their antispasmodic and antihypoxic properties; Pharmaceutical Chemistry Journal; Vol. 28, iss. 5 - Bakibaev A. A. Abdigali Abdimanapovich; Gorshkova V. K.; Arbit O. V.; Filimonov V. D. Viktor Dmitrievich; Saratikov A. S. (1994, 1994)
Title screen